ZapA, a possible virulence factor from Proteus mirabilis exhibits broad protease substrate specificity - Anéas, M.A.F.; Portaro, F.C.V.; Lebrun, I.; Juliano, L.; Palma, Mario Sergio [UNESP]; Fernandes, B.L. (Associação Brasileira de Divulgação Científica (ABRADIC), 2001)
The opportunistic bacterium Proteus mirabilis secretes a metalloprotease, ZapA, considered to be one of its virulence factors due to its IgA-degrading activity. However, the substrate specificity of this enzyme has not yet been fully characterized. In the present study we used fluorescent peptides derived from bioactive peptides and the oxidized ß-chain of insulin to determine the enzyme specificity. The bradykinin- and dynorphin-derived peptides were cleaved at the single bonds Phe-Ser and Phe-Leu, with catalytic efficiencies of 291 and 13 mM/s, respectively. Besides confirming already published cleavage sites, a novel cleavage site was determined for the ß-chain of insulin (Val-Asn). Both the natural and the recombinant enzyme displayed the same broad specificity, demonstrated by the presence of hydrophobic, hydrophilic, charged and uncharged amino acid residues at the scissile bonds. Native IgA, however, was resistant to hydrolysis by ZapA.
Keywords: Proteus mirabilis; metalloprotease; substrate specificity; fluorogenic peptides; IgA; insulin ß-chain